Trabajo y cohesión social en el ámbito urbano : tensiones y desafíos en la sociedad de mercado chilena - Guillermo Wormald; Maria Paz Trebilcock (IdeAs)
In the context of an increasingly globalized society – such as the one developing in Chile during recent decades –, the processes of flexibilization and segmentation of employment opportunities, as well as that of growing workers’ individualization, tend to undermine social cohesion. At the same time, another consequence of this process has been a new appreciation of « work » as a space enabling workers to socialize, which is increasingly perceived as a shared social value. This positive appropriation of work is especially characteristic of urban spaces, among the middle-class, where cohesion relies upon the value of « work », even « hard work », as well as on the prospect of social mobility thanks to work. Today, these two processes combine to create both tensions and challenges in the labor market and gives rise to the concept of social cohesion.This article explores the relationship between workplace transformations and the new meaning of social cohesion in this context. To this end, the authors analyze the socio-economic survey CASEN, whose aim is to identify the characteristics that prevail at work and involve urban workers. The study has been conducted in the cities of La Serena, Coquimbo, Valparaiso, Viña del Mar and Santiago de Chile as part of the following global project: « Integration and Social Cohesion in Chilean Cities » (Soc-24).